An analysis of food security in Malaysia: Does fertility rate matters? - Khor, Yun Chi; Tan, Jia Lin; Tan, Jin Jie; Toh, Jing Wen (2023)
Human cultures have battled throughout history to guarantee that everyone has access to adequate food ensuring an active and healthy life. Having access to enough food persists as a pressing issue at the intersection of nature, society, and technology although there is a significant worldwide endeavor in this era. Food security can be defined as a condition that all individuals are capable of accessing enough, nutritious and safe food physically, socially and economically. This paper contributes to the literature related to the independent variable that led to the food security problem in Malaysia from 1990 to 2019. The independent variable included are Carbon Dioxide Emission, Gross Domestic Product, and Fertility Rate as well as food security in Malaysia be the dependent variable in the research. Fertility rate will be our main focus in this study. There are three theories supporting this study: Neo Malthusian Theory, Anthropogenic Global Warming Theory and Keynesian Theory. Several tests such as ADF Test, ARDL Bounds Test, Error Correction Model, ARCH Test, LM Test, CUSUM Test, VIF Test and Normality Test have been used to test the model. This study has proven that all of the independent variables (Carbon Dioxide Emission, Gross Domestic Product, and Fertility Rate) have a significant relationship with the dependent variable (food security in Malaysia) in the long run.